Penggunaan Kapur Tohor dan Abu Vulkanik pada Bata Ringan Terhadap Berat Jenis, Daya Serap Air, dan Kuat Tekan - Muhamad Iqbal Paundra Karna; Hafizh Fachru Asy’ari; Shifa Fauziyah; Riza Susanti (Jurnal Sipil dan Arsitektur, 2024)
Light brick is a material commonly used in building walls besides red brick. Quick lime and volcanic ash were used in this research as substitute materials for making CLC lightweight bricks. This research aims to analyze using quicklime as a cement substitute and volcanic ash as a sand substitute to test density, water absorption capacity, and compressive strength. Light brick testing refers to the SNI standards for wall masonry. This research also compares the production costs of substitute lightweight bricks with conventional ones. The method used is quantitative experimentation and data analysis techniques using regression analysis. The influencing variable in this research is the independent variable, namely the use of volcanic ash: quicklime in variation A 0%: 0%, variation B 9%: 15%, variation C 9%: 30%, and variation D 9%: 45%. Based on the test results, it can be concluded that using volcanic ash affects increasing density and compressive strength and reduces the value of water absorption capacity. The optimum test results were in Variation D with an average density value of 956 kg/m3, water absorption value of 17%, and compressive strength value of 2.08 MPa.